Strategy Development of Revolving Fund for Small Business Grocery Store Using Information System - Arasy Alimudin; Agus Sukoco; Achmad Zakki Falani (LPPM of NAROTAMA UNIVERSITY, 2021)
Purpose: This study aims at analyzing the factors influencing the ability to return capital of MSMEs in Indonesia (case study of grocery store in Surabaya). Design/methodology/approach: The sample in this study is 171 pioneering grocery stores of cooperative Crosstabulation analysis was implemented to seek the relationship between factors of store internal resources and indicators of quality cooperatives on the ability to pay MSMEs. After that, a system architechture was designed which is then formulated in fuzzy logic to create decision-making system using MYSQL database. To compare the decision result using fuzzy logic, the data obatained were analyzed using logistic regression. Findings: This study was found the results of manual calculations using logistic regression and calculation results using fuzzy logic-based information system application at www.simtokop.net, it is obtained the same recommendation on six stores that have output: “Growing” (eligible getting the revolving fund). Paper type: Research paper